USING INNOVATIVE TECHNOLOGIES IN TEACHING IT AND INFORMATION TECHNOLOGIES - Botirov Muzaffarjon Mansurovich (International Journal of Innovations in Engineering Research and Technology, 2022)
This article provides instructions and suggestions on the use of innovative technologies in the teaching of informatics and information technologies.